1995
DOI: 10.1042/bj3120433
|View full text |Cite
|
Sign up to set email alerts
|

Locally formed dopamine modulates renal Na-Pi co-transport through DA1 and DA2 receptors

Abstract: The involvement of dopamine (DA) receptor subtypes in regulation of renal phosphate transport by DA, either exogenous or locally synthesized from L-dihydroxyphenylalanine (L-dopa) was evaluated in opossum kidney (OK) cells with proximal tubular phenotype. DA synthesis from L-dopa by OK cells was abolished by carbidopa and benserazide, two dissimilar inhibitors of aromatic L-amino acid decarboxylase. L-Dopa stimulated cyclic AMP generation and inhibited Na-dependent Pi uptake, and these effects were abolished b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…7 Moreover, in concert with a D 1 -like agonist, a D 2 -like agonist acts synergistically to inhibit Na ϩ -K ϩ -ATPase and sodium hydrogen exchanger activity in RPT cells and brain striatal cells and sodium-phosphate cotransport activity in opossum kidney cells. [3][4][5] The Our studies show that in the maximally vasorelaxed mesenteric artery, a D 1 receptor agonist (fenoldopam) or a D 3 receptor agonist, PD128907, a 120-fold selectivity over the D 2 receptor 26 has no effect on vascular contractility, in agreement with our previous report. 23 The current studies also support our previous report of the vasorelaxant effect of D 1 or D 3 receptors; D 1 -like receptor-induced vasorelaxation is increased with D 3 receptor activation in WKY rats.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…7 Moreover, in concert with a D 1 -like agonist, a D 2 -like agonist acts synergistically to inhibit Na ϩ -K ϩ -ATPase and sodium hydrogen exchanger activity in RPT cells and brain striatal cells and sodium-phosphate cotransport activity in opossum kidney cells. [3][4][5] The Our studies show that in the maximally vasorelaxed mesenteric artery, a D 1 receptor agonist (fenoldopam) or a D 3 receptor agonist, PD128907, a 120-fold selectivity over the D 2 receptor 26 has no effect on vascular contractility, in agreement with our previous report. 23 The current studies also support our previous report of the vasorelaxant effect of D 1 or D 3 receptors; D 1 -like receptor-induced vasorelaxation is increased with D 3 receptor activation in WKY rats.…”
Section: Discussionsupporting
confidence: 81%
“…In vitro studies have shown that a D 2 -like receptor, in concert with a D 1 -like receptor, synergistically decreases Na ϩ -K ϩ -ATPase, sodium-phosphate co-transporter, and sodium hydrogen exchanger activities in renal proximal tubule and other cells. [3][4][5] In rats, during conditions of normal sodium load, and especially with increased sodium load, D 1 -like and D 2 -like receptors interact to increase sodium excretion. 1,2,6,7 The D 1 -like receptor interacting with the specific D 2 -like receptor subtype in renal sodium transport is unknown.…”
mentioning
confidence: 99%
“…In the proximal tubule where 50 -60% of NaCl and water is reabsorbed, DA inhibits the basolateral membrane Na ϩ ,K ϩ -ATPase (34 -38), which is the primary driving force for transepithelial Na ϩ absorption. In addition, DA also inhibits two apical Na ϩ -coupled transporters, the Na ϩ -coupled inorganic phosphate transporter (92)(93)(94)(95)(96)) and the Na ϩ /H ϩ exchanger NHE3 (27)(28)(29)(30)(31)(32)(33). In addition to transcellular Na ϩ flux, inhibition of NHE3 also reduces the driving force for paracellular NaCl transport (97).…”
Section: Discussionmentioning
confidence: 99%
“…Although no flux measurements have been made in the collecting duct, DA inhibits Na ϩ -K ϩ -ATPase in this segment, which is expected to decrease transepithelial Na ϩ absorption (101). In the proximal tubule where the most significant quantity of Na ϩ absorption occurs, DA decreases Na ϩ flux (18,20) by inhibiting three Na ϩ transporters: the Na ϩ /H ϩ exchanger-3 (NHE3) (2,12,36,39,59,92,108,109) and Na ϩ -phosphate cotransporter -IIa (NaPi-IIa) (11,13,42,72,85) on the apical membrane, and the Na ϩ -K ϩ -ATPase on the basolateral membrane (8,21,22). In the mammalian renal proximal tubule, the synthesis, metabolism, release, and target action of dopamine all take place in the same cells, thus constituting a genuine self-sufficient autocrine-paracrine natriuretic system.…”
mentioning
confidence: 99%